Cobalt-molybdenum bimetallic composite material, preparation method thereof and application thereof to promoting her, oer and overall water splitting three-function reactions
Patent Information
- Application Number
- CN202311342680.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-10-17
AI Technical Summary
Existing non-precious metal catalysts exhibit poor reactivity in electrocatalytic water splitting, have limited catalytic functions, and are difficult to simultaneously and efficiently promote HER, OER, and total water splitting reactions.
Co4S3/CoMoO3 composite material was grown on a nickel foam skeleton by hydrothermal post-annealing. By controlling the ratio of cobalt source, molybdenum source and organic sulfur source and the annealing conditions, a porous nanosheet structure was formed, exposing abundant active sites.
The overpotential in the hydrogen evolution reaction is less than 100 mV, the overpotential in the oxygen evolution reaction is less than 230 mV, and the total water splitting potential is less than 1.6 V, which significantly improves the catalytic activity and outperforms commercial noble metal catalysts.
Smart Images

Figure CN117448873B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of inorganic nanomaterials and catalyst preparation, and particularly to a cobalt-molybdenum bimetallic composite material, its preparation method, and its application in promoting trifunctional reactions such as HER, OER, and total water splitting. Background Technology
[0002] The rapid decline of non-renewable energy and the environmental problems caused by massive greenhouse gas emissions have prompted people to actively seek ways to develop clean energy. Hydrogen (H2) is considered the most promising fuel due to its high energy density, renewability, and environmental friendliness. Against this backdrop, electrocatalytic water splitting (2H2O→2H2+O2) is considered a potential route for green hydrogen production. Water electrolysis involves two half-reactions: the cathode hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction (OER), and this strategy requires a theoretical voltage of 1.23V.
[0003] To date, Pt-based materials are generally considered the most active catalysts for hydrogen evolution reaction (HER). However, their slow kinetics for oxygen evolution reaction (OER) result in low conversion efficiency for hydrogen production via water electrolysis. Currently, the most active OER catalysts are primarily expensive RuO2 and IrO2. However, the scarcity, high cost, and limited functionality of precious metals restrict their further large-scale application.
[0004] Therefore, developing a high-performance, cost-effective, non-precious metal, and earth-element-rich bifunctional HER and OER catalyst to replace precious metal materials remains a challenge.
[0005] Currently, existing non-precious metal materials still suffer from poor reactivity and limited catalytic function. When the current density is 10 mA·cm⁻¹ -2 At that time, the voltage of hydrogen evolution reaction generally exceeds 100mV, the voltage of oxygen evolution reaction generally exceeds 300mV, and the voltage of total water splitting generally exceeds 1.6V.
[0006] Patent CN 113089018 A, published on July 9, 2021, discloses a method for preparing a molybdenum disulfide-cobalt sulfide@passivation layer and its novel applications. First, a composite substrate containing molybdenum disulfide and cobalt sulfide is prepared using a solution method. Then, an alkali-resistant passivation layer is loaded onto the molybdenum disulfide-cobalt sulfide substrate. Cobalt sulfide exhibits excellent electrocatalytic oxygen evolution reaction (OER) performance. The composite of molybdenum disulfide and cobalt sulfide promotes both water splitting and the stability of cobalt sulfide. Applying an alkali-resistant passivation layer further enhances its stability. The prepared molybdenum disulfide-cobalt sulfide@passivation layer electrode exhibits excellent electrocatalytic oxygen evolution reaction (OER) activity. However, it does not disclose how to obtain a trifunctional catalyst for HER, OER, and total water splitting.
[0007] Therefore, the development of non-precious metal-based catalysts still warrants further exploration. Summary of the Invention
[0008] The purpose of this invention is to provide a cobalt-molybdenum bimetallic composite material and its preparation method. Using a nickel foam framework as a skeleton, a Co4S3 / CoMoO3 composite material is grown via a hydrothermal followed by annealing. In the first step, smooth nanosheets are grown on the nickel foam using hydrothermal treatment. In the second step, high-temperature hydrogen-argon annealing causes water molecules to escape and the crystal lattice to shrink due to the increased temperature, resulting in the nanosheets shrinking from the inside and disintegrating into numerous small nanoparticles. While the outline of the nanosheets is still maintained, the interior is no longer a smooth surface but rather composed of a large number of sequentially arranged nanoparticles. These porous nanosheets expose abundant active sites, which is beneficial for improving the catalytic activity of the catalyst. Furthermore, the catalytic efficiency of this catalyst is significantly superior to that of commercial noble metal catalysts. Moreover, the preparation method of this invention is simple, the raw materials are readily available, and it holds promise for large-scale production.
[0009] Another objective of this invention is to provide a cobalt-molybdenum bimetallic composite material for promoting the trifunctional reactions HER, OER, and total water splitting, exhibiting excellent performance. When applied in the hydrogen evolution reaction, this cobalt-molybdenum bimetallic composite material performs well at a current density of 10 mA cm⁻¹. -2 At this time, the overpotential is less than 100mV, and more preferably only 48mV; when applied in the oxygen evolution reaction, at a current density of 10mAcm -2 When the overpotential is less than 230mV, more preferably only 183mV; when used in the complete water splitting process, the catalyst potential is less than 1.6V, preferably only 1.46V.
[0010] The specific technical solution of this invention is as follows:
[0011] The present invention provides a method for preparing a cobalt-molybdenum bimetallic composite material, comprising the following steps:
[0012] 1) Mix cobalt source, molybdenum source and organic sulfur source in solvent, add nickel foam, and heat to react;
[0013] 2) Anneal the product from step 1) to obtain the Co4S3 / CoMoO3 composite material.
[0014] In step 1), a heating reaction is carried out, during which the precursor will grow on the nickel foam.
[0015] In step 1), the molar ratio of the cobalt source, molybdenum source, and organic sulfur source is (1-2.8):(0.1-0.4):(1.5-3.9); more preferably, it is 2:0.26:3.
[0016] In step 1), the cobalt source is a soluble cobalt salt; preferably cobalt nitrate hexahydrate Co(NO3)2·6H2O;
[0017] In step 1), the molybdenum source is a soluble molybdenum salt; preferably ammonium molybdate tetrahydrate (NH4)6Mo7O 24 ·4H2O;
[0018] In step 1), the organic sulfur source is selected from thiourea;
[0019] In step 1), the solvent is selected from water, preferably deionized water;
[0020] In step 1), the concentration of the cobalt source in the solvent is 0.05–0.14 M;
[0021] In step 1), the heating reaction is carried out at a temperature of 70℃ to 160℃ for 5 hours to 24 hours; preferably, it is carried out at 100℃ for 8 hours.
[0022] In step 1), the area of the nickel foam is 2-10 cm². 2 .
[0023] In step 1), after the reaction is complete, allow the nickel foam to cool naturally at room temperature and remove it. Then, rinse the nickel foam several times with deionized water and ethanol to remove impurities adhering to the surface, and dry it in a vacuum drying oven to obtain a brown precursor, which is then stored for later use; the vacuum drying temperature is 45-80℃.
[0024] In step 2), the annealing is carried out at a temperature of 550–650°C for 1–3 hours; the annealing atmosphere is hydrogen and argon.
[0025] Preferably, in step 2), the annealing refers to placing the nickel foam containing the precursor in a mixed atmosphere composed of hydrogen and argon; the heating rate should be maintained between 1 and 10 °C / min, raising the temperature to 550 to 650 °C and holding it for 1 to 3 hours; the hydrogen volume percentage is 5% to 20%.
[0026] In step 2), the preferred annealing conditions are: heating at a rate of 5°C / min to 600°C, and performing annealing at this temperature for 2 hours; in the mixed atmosphere, hydrogen accounts for 10% of the gas volume.
[0027] In step 2), after annealing, the resulting product is allowed to cool naturally. The product is black.
[0028] The Co4S3 / CoMoO3 composite material prepared in this invention mainly involves: placing a cobalt source, a molybdenum source, thiourea, and nickel foam in a reactor for a hydrothermal reaction, growing sulfur-doped cobalt molybdate hydrate (CoMoO4·0.75H2O) on the nickel foam. Then, partial reduction is carried out in a tube furnace under a hydrogen-argon mixture. During this annealing process, the escape of oxygen and changes in the crystal lattice due to the flow of gas and water molecules cause the nanosheets to shrink from the inside, disintegrating into numerous small nanoparticles, forming a large number of defects and amorphous regions, exposing abundant active sites. Hydrogen acts as a reducing agent, converting high-valence Mo into lower-valence CoMoO3, while some Co bonds with S to form Co4S3. The resulting nanoparticles aggregate into a nanosheet structure with abundant nanochannels, which helps expose more active surface area and facilitates rapid electron transfer, accelerating the reaction and thus exhibiting high catalytic activity. If the molybdenum source is replaced with sodium molybdate, the desired morphology cannot be synthesized, resulting in nanorods. If the hydrothermal temperature is too high, the morphology of the product will change dramatically, resulting in larger columnar structures. The larger size and structure are not conducive to sufficient contact with the reactants, thus affecting the performance. If the amount of thiourea is increased or the annealing temperature is raised, the structure of the product will collapse, thus affecting the performance.
[0029] The cobalt-molybdenum bimetallic composite material provided by this invention is prepared by the above method. It is a Co4S3 / CoMoO3 composite material, which is a nanosheet with a porous structure composed of self-assembled nanoparticles. The particles are Co4S3 / CoMoO3 composite material, the side length of the nanosheets ranges from 0.5 to 1 μm, the thickness of the nanosheets is 20 to 80 nm, preferably 30 to 40 nm, and the gap between the nanoparticles is 1 to 40 nm, preferably 2 to 6 nm.
[0030] Another objective of this invention is to provide a cobalt-molybdenum bimetallic composite material for promoting the application of HER, OER and total water splitting trifunctional reactions, with excellent performance.
[0031] The application of the cobalt-molybdenum bimetallic composite material Co4S3 / CoMoO3 provided by this invention in the hydrogen evolution reaction of water electrolysis; specifically: at room temperature, it exhibits an overpotential of 48mV in 1M KOH electrolyte solution, and the lower the overpotential, the better the catalytic activity.
[0032] The application of the cobalt-molybdenum bimetallic composite material Co4S3 / CoMoO3 provided by this invention in the oxygen evolution reaction of water electrolysis; specifically, it exhibits an overpotential of 183 mV in a 1M KOH electrolyte solution at room temperature. The lower the overpotential, the better the catalytic activity.
[0033] The application of the cobalt-molybdenum bimetallic composite material Co4S3 / CoMoO3 provided by this invention in the complete water splitting process.
[0034] Compared with existing technologies, the Co4S3 / CoMoO3 composite material provided by this invention utilizes the polymorphism exhibited by Mo and its strong binding effect on H. The Co4S3 / CoMoO3 composite material, prepared by combining Co and Mo sources with other ligands, can be used as a water electrolysis catalyst. The interfacial Mo atoms in CoMoO3 can provide active sites for the dissociation of water molecules, which is more conducive to the reaction. The Co4S3 / CoMoO3 composite material provided by this invention is a porous nanosheet composed of self-assembled nanoparticles, exposing more active sites. It exhibits excellent performance in promoting trifunctional reactions such as HER, OER, and total water splitting. Attached Figure Description
[0035] Figure 1 This is a scanning electron microscope image of the Co4S3 / CoMoO3 composite material synthesized in Example 1 at 30K; the nanoparticle size is approximately 35-40 nm, and the pore size is approximately 4-6 nm.
[0036] Figure 2 This is a scanning electron microscope image of the Co4S3 / CoMoO3 composite material synthesized in Example 1 at 70 K;
[0037] Figure 3 The image shows the X-ray diffraction (XRD) pattern of the Co4S3 / CoMoO3 composite material synthesized in Example 1.
[0038] Figure 4 The HER polarization curves of the materials synthesized in Examples 1, 2, 3 and 4 in 1M KOH solution are shown.
[0039] Figure 5 The OER polarization curves of the materials synthesized in Examples 1, 2, 3 and 4 in 1M KOH solution are shown.
[0040] Figure 6 The image shows the total hydrolysis polarization curve of the Co4S3 / CoMoO3 composite material synthesized in Example 1 in 1M KOH solution;
[0041] Figure 7 The image shows a scanning electron microscope (SEM) image of the material synthesized in Comparative Example 1.
[0042] Figure 8 The image shows a scanning electron microscope (SEM) image of the material synthesized in Comparative Example 2.
[0043] Figure 9 The image shows a scanning electron microscope (SEM) image of the material synthesized in Comparative Example 3.
[0044] Figure 10 The image shown is a scanning electron microscope (SEM) image of the precursor synthesized in step 1) in Example 1.
[0045] Figure 11The image shows a scanning electron microscope (SEM) image of the material synthesized in Comparative Example 4.
[0046] Figure 12 HER polarization curves of the materials synthesized in Comparative Examples 1, 2, 3 and 4 in 1M KOH solution;
[0047] Figure 13 The image shows a scanning electron microscope (SEM) image of the material synthesized in Comparative Example 5.
[0048] Figure 14 This is a scanning electron microscope image of the material synthesized in Comparative Example 6. Detailed Implementation
[0049] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.
[0050] Example 1
[0051] A method for preparing a cobalt-molybdenum bimetallic composite material includes the following steps:
[0052] 1) Preparation of precursors for nickel foam: Weigh 2 mmol Co(NO3)2·6H2O and 0.26 mmol (NH4)6Mo7O respectively. 24 4H₂O and 3 mmol thiourea were dissolved in 20 mL of deionized water and stirred magnetically for 10 min. The reaction solution was then transferred to a polytetrafluoroethylene (PTFE) reactor of appropriate volume. A piece of cleaned nickel foam was then tilted and placed into the solution. The autoclave was then sealed and placed in a forced-air drying oven for heating at 100°C for 8 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The nickel foam was then removed and rinsed five times with deionized water and ethanol to remove impurities adhering to the surface. It was then dried in a vacuum drying oven to obtain a brown precursor, which was analyzed by scanning electron microscopy. Figure 10 Observe its appearance.
[0053] Store for later use; these are smooth nanosheets.
[0054] 2) Preparation of Co4S3 / CoMoO3 composite material: Nickel foam containing precursor was placed in a mixed atmosphere of H2 and Ar gas for heat treatment, with a volume ratio of H2 to Ar gas of 10:90; the heating rate was 5℃ / min, and the temperature was raised to 600℃ and held for 2 hours; after annealing, the product was allowed to cool naturally, and the product was black at this time.
[0055] The Co4S3 / CoMoO3 composite material prepared according to the above method was analyzed by scanning electron microscopy. Figure 1 and Figure 2 Its morphology was observed, confirming it as a nanosheet structure assembled from nanoparticles. X-ray diffraction was then performed. Figure 3Further evidence confirms that the material is a Co4S3 / CoMoO3 composite material, with XRD results showing Co4S3 and CoMoO3. This demonstrates that the Co4S3 / CoMoO3 composite material was successfully prepared in this invention.
[0056] Example 2
[0057] A method for preparing a cobalt-molybdenum bimetallic composite material includes the following steps:
[0058] 1) Preparation of precursors for nickel foam: Weigh 2.5 mmol Co(NO3)2·6H2O and 0.18 mmol (NH4)6Mo7O respectively. 24 • 4H₂O and 2.6 mmol thiourea were dissolved in 20 mL of deionized water and stirred magnetically for 10 min. The reaction solution was then transferred to a polytetrafluoroethylene (PTFE) reactor of appropriate volume, and a piece of cleaned nickel foam was tilted and placed into the solution. The autoclave was then sealed and placed in a forced-air drying oven for heating at 100°C for 8 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the nickel foam was removed. Subsequently, the nickel foam was washed four times with deionized water and ethanol to remove impurities adhering to the surface, and then dried in a vacuum drying oven to obtain a brown precursor, which was stored for later use.
[0059] 2) Preparation of Co4S3 / CoMoO3 composite material: Nickel foam containing the precursor was heat-treated in a mixed atmosphere of H2 and Ar gases with a volume ratio of 10:90; the heating rate was 5℃ / min, and the temperature was raised to 600℃ and held for 2 hours. After annealing, the product was allowed to cool naturally, at which point the product was black.
[0060] Example 3
[0061] A method for preparing a cobalt-molybdenum bimetallic composite material includes the following steps:
[0062] 1) Preparation of precursors for nickel foam: Weigh 2 mmol Co(NO3)2·6H2O and 0.26 mmol (NH4)6Mo7O respectively. 24 4H₂O and 3 mmol of thiourea were dissolved in 20 mL of deionized water and stirred magnetically for 10 min. The reaction solution was then transferred to a polytetrafluoroethylene (PTFE) reactor of appropriate volume, and a piece of cleaned nickel foam was tilted into the solution. The autoclave was then sealed and placed in a forced-air drying oven for heating at 100°C for 8 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the nickel foam was removed. Subsequently, the nickel foam was rinsed four times with deionized water and ethanol to remove impurities adhering to the surface, and then dried in a vacuum drying oven to obtain a brown precursor, which was stored for later use.
[0063] 2) Preparation of Co4S3 / CoMoO3 composite material: Nickel foam containing the precursor was heat-treated in a mixed atmosphere of H2 and Ar, with hydrogen comprising 5% and argon comprising 95%, at a heating rate of 5℃ / min, reaching 600℃ and holding for 2 hours. After annealing, the product was allowed to cool naturally, at which point the product was black.
[0064] Example 4
[0065] A method for preparing a cobalt-molybdenum bimetallic composite material includes the following steps:
[0066] 1) Preparation of precursors for nickel foam: Weigh 2 mmol Co(NO3)2·6H2O and 0.26 mmol (NH4)6Mo7O respectively. 24 4H₂O and 3 mmol of thiourea were dissolved sequentially in 20 mL of deionized water, and the mixture was magnetically stirred for 10 min. The reaction solution was then transferred to a polytetrafluoroethylene (PTFE) reactor of appropriate volume, and a piece of cleaned nickel foam was tilted and placed into the solution. The autoclave was then sealed and placed in a forced-air drying oven for heating at 120°C for 8 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the nickel foam was removed. Subsequently, the nickel foam was rinsed four times with deionized water and ethanol to remove impurities adhering to the surface, and then dried in a vacuum drying oven to obtain a brown precursor, which was stored for later use.
[0067] 2) Preparation of Co4S3 / CoMoO3 composite material: Nickel foam containing the precursor was heat-treated in a mixed atmosphere of H2 and Ar, with hydrogen comprising 10% and argon comprising 90%. The heating rate was 5℃ / min, and the temperature was raised to 600℃ and held for 2 hours. After annealing, the product was allowed to cool naturally, at which point the product was black.
[0068] Comparative Example 1
[0069] The procedure was carried out according to Example 1, except that the amount of Co(NO3)2·6H2O was [missing information]. 3mmol , (NH4)6Mo7O 24 ·4H2O The amount was 0.095 mmol. Everything else is the same as in Example 1.
[0070] Scanning electron microscopy Figure 7 Observing the morphology of Comparative Example 1, it was observed that the material prepared according to the above method did not form a nanosheet structure assembled from nanoparticles on the nickel foam framework, and the surface of the nickel foam contained amorphous substances. This indicates that the ratio of cobalt source to molybdenum source can control the morphology of the material to a certain extent.
[0071] Comparative Example 2
[0072] The process was carried out according to Example 1, except that the reaction vessel was placed in a forced-air drying oven for heating and reaction at a temperature of [temperature missing]. 170℃ Everything else is the same as in Example 1.
[0073] Scanning electron microscopy Figure 8 Observing the morphology of Comparative Example 2, it was observed that the material prepared according to the above method did not form nanosheet structures assembled from nanoparticles on the nickel foam framework, but rather large nanorod-like substances were generated on the surface of the nickel foam. This indicates that the reaction temperature can control the morphology of the material to a certain extent. This may be because excessively high reaction temperatures, differences in surface energy and crystal growth rates during the crystal growth process, etc., cause the molybdenum compound crystals to grow in a specific direction, thereby forming nanorod structures.
[0074] Comparative Example 3
[0075] The procedure is the same as in Example 1, except that: During annealing, the heat treatment is carried out in pure Ar gas. Everything else is the same as in Example 1.
[0076] Scanning electron microscopy Figure 9 Observing the morphology of Comparative Example 3, it was observed that the material prepared according to the above method did not form a nanosheet structure assembled from nanoparticles on the nickel foam framework. Instead, unevenly sized and shapeless particles were attached to the surface of the nickel foam. This indicates that Ar annealing caused the collapse of the material structure.
[0077] Comparative Example 4
[0078] Performed according to Example 1, the difference being: (NH4)6Mo7O 24 ·4H2O is replaced with Na2MoO4·2H2O. Everything else is the same as in Example 1.
[0079] Scanning electron microscopy Figure 11 Observing the morphology of Comparative Example 4, it was found that the material obtained according to the above preparation method did not form a nanosheet structure assembled from nanoparticles on the nickel foam skeleton, but rather a nanorod structure.
[0080] Comparative Example 5
[0081] The procedure is the same as in Example 1, except that: The amount of thiourea was 4 mmol. Everything else is the same as in Example 1.
[0082] Scanning electron microscopy Figure 13 Observing the morphology of Comparative Example 5, it was found that the material obtained by the above preparation method had uneven shape and size, indicating that the structure had collapsed.
[0083] Comparative Example 6
[0084] The procedure is the same as in Example 1, except that: The annealing temperature is 700℃. Everything else is the same as in Example 1.
[0085] Scanning electron microscopy Figure 14 Observing the morphology of Comparative Example 6, it was observed that the material obtained according to the above preparation method collapsed on the nickel foam skeleton.
[0086] Application Example 1
[0087] The application of Co4S3 / CoMoO3 composite materials in the hydrogen evolution reaction is as follows:
[0088] The HER polarization curves of the Co4S3 / CoMoO3 composite material under alkaline conditions were obtained by electrochemical linear sweep voltammetry. Specifically, at room temperature, a three-electrode system was formed using a 1cm × 2cm sample of the products from Examples 1, 2, and 3 as the working electrode, a silver chloride electrode as the reference electrode, and a carbon rod as the counter electrode. The electrolyte was a 1M potassium hydroxide solution. A CHI760 electrochemical workstation was used, with a potential range of 0 to -0.8V (vs. HER), and a 5mV ss method. -1 The scan rate was set, and 90% iR compensation was applied to obtain the polarization curve of HER. At a current density of 10 mA cm⁻¹ -2 At that time, the overpotential of the catalyst prepared in Example 1 was only 48mV.
[0089] Figure 4 The images show the HER polarization curves of the products from Examples 1, 2, 3, and 4 in 1M KOH solution. Specifically, the polarization curves were obtained at a current density of 10 mA cm⁻¹. -2 At that time, the overpotential of the catalyst prepared in Example 1 was only 48mV, the overpotential of the catalyst prepared in Example 2 was 96mV, the overpotential of the catalyst prepared in Example 3 was 65mV, and the overpotential of the catalyst prepared in Example 4 was 81mV. The overpotentials of the above examples were all less than 100mV, which shows excellent catalytic performance. Figure 12 The HER polarization curves of the products of Comparative Examples 1, 2, 3, and 4 in 1M KOH solution are shown. Specifically, at a current density of 10 mA cm⁻¹ -2 At that time, the overpotential of the catalyst prepared in Comparative Example 1 was 271 mV, the overpotential of the catalyst prepared in Comparative Example 2 was 318 mV, the overpotential of the catalyst prepared in Comparative Example 3 was 266 mV, and the overpotential of the catalyst prepared in Comparative Example 4 was 204 mV. The overpotentials of the above examples were all much greater than 100 mV, indicating that the catalytic activity was low.
[0090] Application Example 2
[0091] The application of Co4S3 / CoMoO3 composite materials in the oxygen evolution reaction is as follows:
[0092] The OER polarization curves of the Co4S3 / CoMoO3 composite material under alkaline conditions were obtained by electrochemical linear sweep voltammetry. Specifically, at room temperature, a three-electrode system was formed using 1cm × 2cm electrodes from Examples 1, 2, and 3 as the working electrode, a silver chloride electrode as the reference electrode, and a platinum sheet as the counter electrode. The electrolyte was a 1M potassium hydroxide solution. A CHI760 electrochemical workstation was used, with a potential range of 1.7–1.1V (vs. RHE) and a voltammetry frequency of 1mV / s. -1 The scan rate was set, and 90% iR compensation was applied to obtain the polarization curve of OER. At a current density of 10 mA cm⁻¹ -2 At that time, the overpotential of the catalyst prepared in Example 1 was only 183mV.
[0093] Figure 5 The OER polarization curves of the products from Examples 1, 2, 3, and 4 in 1M KOH solution are shown. Specifically, at a current density of 10 mA cm⁻¹ -2 At that time, the overpotential of the catalyst prepared in Example 1 was only 183 mV, the overpotential of the catalyst prepared in Example 2 was 215 mV, the overpotential of the catalyst prepared in Example 3 was 221 mV, and the overpotential of the catalyst prepared in Example 4 was 203 mV. The overpotentials of the above examples were all less than 300 mV, which shows excellent catalytic performance.
[0094] Application Example 3
[0095] The application method of Co4S3 / CoMoO3 composite material in water hydrolysis is as follows:
[0096] The total water splitting polarization curves of the Co4S3 / CoMoO3 composite material under alkaline conditions were obtained by electrochemical linear sweep voltammetry. Specifically, at room temperature, two 1cm × 2cm plates from Example 1 were used as the cathode and anode, respectively. The electrolyte was a 1M potassium hydroxide solution. A CHI760 electrochemical workstation was used, with a potential range of 1.7–1.2V (vs. RHE) and a sweep voltammetry of 1mV. -1 The scanning rate was set, and 90% iR compensation was applied to obtain the polarization curves for the complete water splitting. At a current density of 10 mA cm⁻¹, the polarization curves for the complete water splitting were obtained. -2 At that time, the potential of the catalyst prepared in Example 1 was only 1.46V, which is much less than 1.6V, indicating that it has excellent catalytic performance.
[0097] Figure 6 The image shows the total hydrolysis polarization curve of the product from Example 1 in 1M KOH solution;
[0098] Compared to precious metal-based catalysts, the raw materials used in this invention are readily available, and the preparation process is simpler, thus significantly reducing production costs. Furthermore, this multifunctional catalyst exhibits excellent performance, simultaneously meeting the requirements of the hydrogen evolution reaction, oxygen evolution reaction, and complete water splitting reaction. From the perspective of environmental protection and sustainable development, the catalyst of this invention is expected to contribute to the development of clean energy, helping to promote energy transition and reduce dependence on non-renewable energy sources.
[0099] The items underlined above do not meet the requirements of this invention.
[0100] The above detailed description of a Co4S3 / CoMoO3 composite material for promoting the three functional applications of HER, OER and total water splitting, with reference to the embodiments, is illustrative rather than limiting. Several embodiments may be listed within the defined scope. Therefore, variations and modifications without departing from the overall concept of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a cobalt-molybdenum bimetallic composite material, characterized in that, The preparation method includes the following steps: 1) Mix cobalt source, molybdenum source and organic sulfur source in solvent, add nickel foam, and heat to react; 2) Anneal the product from step 1) to obtain the Co4S3 / CoMoO3 composite material; The molar ratio of the cobalt source, molybdenum source, and organic sulfur source is (1~2.8):(0.1~0.4):(1.5~3.9). In step 1), the molybdenum source is (NH4)6Mo7O 24 ·4H2O; In step 1), the organic sulfur source is selected from thiourea; In step 1), the heating reaction is carried out at a temperature of 70℃~160℃ for 5 h~24 h; In step 2), the annealing is carried out at a temperature of 550~650℃ for 1~3 hours; the annealing atmosphere is hydrogen and argon.
2. The preparation method according to claim 1, characterized in that, In step 1), the solvent is selected from water.
3. The preparation method according to claim 1, characterized in that, In step 1), the concentration of the cobalt source in the solvent is 0.05~0.14 M.
4. The preparation method according to claim 1, characterized in that, In step 2), the annealing process involves hydrogen with a volume percentage of 5% to 20%.
5. A cobalt-molybdenum bimetallic composite material prepared by the preparation method according to any one of claims 1-4, characterized in that, The cobalt-molybdenum bimetallic composite material is a Co4S3 / CoMoO3 composite material, which is a porous nanosheet self-assembled from nanoparticles. The nanosheet has a side length range of 0.5~1 μm, a thickness of 20~80 nm, and a gap of 1~40 nm between nanoparticles.
6. The application of a cobalt-molybdenum bimetallic composite material prepared by the preparation method according to any one of claims 1-5, characterized in that, Applications that promote HER, OER, and total hydrolysis trifunctional reactions.
Citation Information
Patent Citations
Preparation method and new application of molybdenum disulfide-cobalt sulfide coated passivation layer
CN113089018A
